Divine Vassal: Ancient Near Eastern Attributes in the Father-Son Imagery of Hosea 11 - Kugler, Gili (Harvard theological review, 2025)
Attributes of familial relationships, ascribed in biblical metaphors to YHWH and Israel, can be traced back to ancient Near Eastern mythological and diplomatic concepts. In Hosea 11, the dynamic between YHWH and Israel mirrors political and authoritarian conventions prevalent in that era. Israel is depicted as an adopted son of God, analogous to an Egyptian or Assyrian monarch whose authority derives from a divine heritage. Simultaneously, Israel assumes the role of a subjugated and devoted son, akin to a vassal subdued according to the norms of the ancient Near East. As a result, the characteristics of the chosen son in Hosea 11 blend attributes of both a king and a vassal, two entities who have no influence over their own chosen status. Consequently, Israel’s position is best described as that of a "divine vassal," one whose privileges are affirmed, while his very existence and territorial rights remain in perpetual jeopardy.